Analysis of effects of stimulation in vitro of ovalbumin primed lymph node cells on adoptive transfer of experimental immune mediated blepharoconjunctivitis in Lewis rats. Issue 10 (1st October 1998) - Yoshida, Hironori; Yoshida, Osamu; Iwamoto, Hiroshi; Nishino, Koji; Hashida, Masatsugu; Fukushima, Atsuki; Ueno, Hisayuki
Abstract : AIM: To analyse the role of stimulation in vitro of lymphocytes on the augmentation of experimental immune mediated blepharoconjunctivitis (EC, formerly EAC) in Lewis rats induced by adoptive transfer. METHODS: Two weeks after immunisation with ovalbumin (OVA), rat draining lymph nodes were collected and 50 × 10 6 cells were injected into naive syngeneic recipients either directly or after culture in vitro with OVA, concanavalin A (Con A), or purified protein derivative (PPD) for 3 days. Four days after injection the rats were topically challenged with OVA. 24 hours later, they were sacrificed and eyes and spleens were harvested for histology and proliferation assay. In some experiments, naive recipient rats were irradiated with 7 Gy γ ray before transfer. The expression of adhesion molecules and cytokine profile of OVA primed lymph node cells were also investigated. RESULTS: Both infiltrated cell number and splenocyte proliferation in the recipients of stimulated cells were higher than those of unstimulated cells. In vitro stimulation with OVA or Con A induced a severe cellular infiltration, while stimulation with PPD did not. Irradiation markedly diminished cellular infiltration. Stimulation in vitro upregulated the CD4/CD8 ratio by four times and augmented expression of CD25, I-A, ICAM-1 molecules on OVA primed lymph node cells by about five times. IFN-γ was detected in OVA primed cells by stimulation in vitro, while IL-4 mRNA was extinguished by stimulation in vitro. CONCLUSIONS: Augmentation of EC by stimulation in vitro of transferred lymphocytes might depend on the upregulation of expression of cell surface molecules and cytokine shift as well as augmented antigen specificity.